Answer:
<h3>6 days</h3>
Step-by-step explanation:
Given the inequality expression of the total cost (c) in dollars of renting a car for n days as c ≥ 125 + 50n
To get the maximum number of days for which a car could be rented if the total cost was $425, substitute c = 425 into the expression and find n
425 ≥ 125 + 50n
Subtract 125 from both sides
425 - 125 ≥ 125 + 50n - 125
300≥ 50n
Divide both sides by 50
300/50≥50n/50
6 ≥n
Rearrange
n≤6
<em>Hence the maximum number of days for which a car could be rented if the total cost was $425 is 6days</em>
<em></em>
A formula is recursive if it expresses the term
in terms of the previous one(s) ![a_{n-1},\ a_{n-2},\ \ldots,\ a_1](https://tex.z-dn.net/?f=%20a_%7Bn-1%7D%2C%5C%20a_%7Bn-2%7D%2C%5C%20%5Cldots%2C%5C%20a_1%20)
In this case, every term is 7 more than the previous one, so the formula for
will only involve
:
![a_n = a_{n-1} + 7](https://tex.z-dn.net/?f=%20a_n%20%3D%20a_%7Bn-1%7D%20%2B%207%20)
In fact, this formula is simply saying: for every index
, the term with that index is 7 more than the term before.
Also, we have to specify the starting point (otherwise we would go backwards indefinitely), so the complete recursive formula is
![a_n = a_{n-1} + 7,\quad a_1 = 2](https://tex.z-dn.net/?f=%20a_n%20%3D%20a_%7Bn-1%7D%20%2B%207%2C%5Cquad%20a_1%20%3D%202%20)
which means: start with 2 and generate every other term by adding 7 to the previous one.
I believe yes, as long as a triangle has 3 sides it is indeed a triangle
Set like terms on each side by adding six to the first side and subtracting 1/2x from the first side. this gives you 9<1.5x. divide both sides by 1.5 to get 66. the answer is 4) x>6
![y'=(t+y)^2-1](https://tex.z-dn.net/?f=y%27%3D%28t%2By%29%5E2-1)
Substitute
, so that
, and
![u'=u^2-1](https://tex.z-dn.net/?f=u%27%3Du%5E2-1)
which is separable as
![\dfrac{u'}{u^2-1}=1](https://tex.z-dn.net/?f=%5Cdfrac%7Bu%27%7D%7Bu%5E2-1%7D%3D1)
Integrate both sides with respect to
. For the integral on the left, first split into partial fractions:
![\dfrac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)=1](https://tex.z-dn.net/?f=%5Cdfrac%7Bu%27%7D2%5Cleft%28%5Cfrac1%7Bu-1%7D-%5Cfrac1%7Bu%2B1%7D%5Cright%29%3D1)
![\displaystyle\int\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)\,\mathrm dt=\int\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%5Cfrac%7Bu%27%7D2%5Cleft%28%5Cfrac1%7Bu-1%7D-%5Cfrac1%7Bu%2B1%7D%5Cright%29%5C%2C%5Cmathrm%20dt%3D%5Cint%5Cmathrm%20dt)
![\dfrac12(\ln|u-1|-\ln|u+1|)=t+C](https://tex.z-dn.net/?f=%5Cdfrac12%28%5Cln%7Cu-1%7C-%5Cln%7Cu%2B1%7C%29%3Dt%2BC)
Solve for
:
![\dfrac12\ln\left|\dfrac{u-1}{u+1}\right|=t+C](https://tex.z-dn.net/?f=%5Cdfrac12%5Cln%5Cleft%7C%5Cdfrac%7Bu-1%7D%7Bu%2B1%7D%5Cright%7C%3Dt%2BC)
![\ln\left|1-\dfrac2{u+1}\right|=2t+C](https://tex.z-dn.net/?f=%5Cln%5Cleft%7C1-%5Cdfrac2%7Bu%2B1%7D%5Cright%7C%3D2t%2BC)
![1-\dfrac2{u+1}=e^{2t+C}=Ce^{2t}](https://tex.z-dn.net/?f=1-%5Cdfrac2%7Bu%2B1%7D%3De%5E%7B2t%2BC%7D%3DCe%5E%7B2t%7D)
![\dfrac2{u+1}=1-Ce^{2t}](https://tex.z-dn.net/?f=%5Cdfrac2%7Bu%2B1%7D%3D1-Ce%5E%7B2t%7D)
![\dfrac{u+1}2=\dfrac1{1-Ce^{2t}}](https://tex.z-dn.net/?f=%5Cdfrac%7Bu%2B1%7D2%3D%5Cdfrac1%7B1-Ce%5E%7B2t%7D%7D)
![u=\dfrac2{1-Ce^{2t}}-1](https://tex.z-dn.net/?f=u%3D%5Cdfrac2%7B1-Ce%5E%7B2t%7D%7D-1)
Replace
and solve for
:
![t+y=\dfrac2{1-Ce^{2t}}-1](https://tex.z-dn.net/?f=t%2By%3D%5Cdfrac2%7B1-Ce%5E%7B2t%7D%7D-1)
![y=\dfrac2{1-Ce^{2t}}-1-t](https://tex.z-dn.net/?f=y%3D%5Cdfrac2%7B1-Ce%5E%7B2t%7D%7D-1-t)
Now use the given initial condition to solve for
:
![y(3)=4\implies4=\dfrac2{1-Ce^6}-1-3\implies C=\dfrac3{4e^6}](https://tex.z-dn.net/?f=y%283%29%3D4%5Cimplies4%3D%5Cdfrac2%7B1-Ce%5E6%7D-1-3%5Cimplies%20C%3D%5Cdfrac3%7B4e%5E6%7D)
so that the particular solution is
![y=\dfrac2{1-\frac34e^{2t-6}}-1-t=\boxed{\dfrac8{4-3e^{2t-6}}-1-t}](https://tex.z-dn.net/?f=y%3D%5Cdfrac2%7B1-%5Cfrac34e%5E%7B2t-6%7D%7D-1-t%3D%5Cboxed%7B%5Cdfrac8%7B4-3e%5E%7B2t-6%7D%7D-1-t%7D)